A Sustainable Green Enzymatic Method for Amide Bond Formation - Orsy György; Shahmohammadi Sayeh; Forró Enikő (2023)
A sustainable enzymatic strategy for the preparation of amides by using Candida antarctica lipase B as the biocatalyst and cyclopentyl methyl ether as a green and safe solvent was devised. The method is simple and efficient and it produces amides with excellent conversions and yields without the need for intensive purification steps. The scope of the reaction was extended to the preparation of 28 diverse amides using four different free carboxylic acids and seven primary and secondary amines, including cyclic amines. This enzymatic methodology has the potential to become a green and industrially reliable process for direct amide synthesis.
Keywords: Kémiai tudományok